Psychometric evaluation of the Indonesian physical education teacher job satisfaction scale (IPET-JSS): development and validation of a contextual job satisfaction instrument for physical education - Gazali, Novri; Perdima, Feby Elra; Setiawan, Edi; Lobo, Joseph; Sari, Merlina (Edu Sportivo: Indonesian Journal of Physical Education, 2025)
Background: Job satisfaction among physical education (PE) teachers is a critical factor influencing instructional quality, work motivation, and long-term professional commitment. However, there is currently no comprehensive and standardized instrument specifically designed to measure the job satisfaction of PE teachers within the Indonesian context. Research Objective: This study aimed to develop and evaluate the psychometric properties of the Indonesian Physical Education Teacher Job Satisfaction Scale (IPET-JSS), an adapted and contextually modified version of Spector’s Job Satisfaction Survey (JSS), tailored specifically for PE teachers in Indonesia. Method: A cross-sectional quantitative survey design was employed. A total of 300 PE teachers from primary, junior secondary, and senior/vocational high schools—both public and private—in Bengkulu City participated. The IPET-JSS comprises 36 items across nine dimensions (pay, promotion, supervision, fringe benefits, contingent rewards, operating procedures, coworkers, nature of work, and communication), rated on a 6-point Likert scale. Construct validity was assessed using confirmatory factor analysis (CFA), and reliability was examined via Cronbach’s alpha and composite reliability (CR). Finding/Results: All items showed factor loadings above 0.50. The Cronbach’s alpha for each dimension ranged from 0.75 to 0.86, and CR values exceeded 0.70, indicating strong internal consistency. Coworkers and Nature of Work were the highest-rated dimensions, while Pay and Operating Procedures received the lowest scores. The CFA results supported a good model fit (CFI > 0.90; RMSEA < 0.08), affirming the structural validity of the IPET-JSS. Conclusion: The IPET-JSS is a psychometrically sound instrument for assessing job satisfaction among Indonesian PE teachers. It holds promise for use in both research and practice, particularly in teacher evaluation, educational policy development, and professional development planning. Future studies are recommended to explore its cross-contextual validity and associations with other psychosocial constructs.